-4x+9y=28
-4x-y=-28
Solve for one variable in either equation, then substitute it in the other equation to find the other variable.
-4x+9y=28
Add 4x to both sides
9y=28+4x
Divide both sides by 9
y=(28+4x) / 9
-4x-y=-28
-4x- ((28+4x) / 9)= -28
-4x-28/9-4x/9=-28
Multiply everything by -9 to get rid of denominators
(-9)(-4x)-(-9)(28/9)-(-9)(4x/9)=(-9)(-28)
36x+28+4x=252
40x+28=252
Subtract 28 from both sides
40x=224
Divide both sides by 40
x=5.6
Substitute x=5.6 back in to now solve for y.
-4x+9y=28
(-4)(5.6)+9y=28
-22.4+9y=28
Add -22.4 to both sides
9y=50.4
Divide both sides by 9
y=5.6
Hope this helps! :)